Putting the economic back into the social (work curriculum) - Barns, Angela; Preston, Alison (Curtin University of Technology, 2003)
Until recently economics and economic theory was regarded as an implicit component of socialwork education. Recent years, however, have hosted a shift in social work education,accompanied by a parallel diminution of economic content within the social work curriculum.This paper considers the repercussions and implications of these educational developments, forsocial work practice and specifically the articulation of social work voices within the public socialpolicy arena. As a means of exploring these themes this paper documents and discusses thedata collected from a survey of fourth year social work students at a Western Australianuniversity. Providing a localized analysis, the survey responses illustrate the degree ofdisconnectedness in student understandings of economic and social phenomenon. Comparativedata from a survey of undergraduate commerce students are similarly employed to highlight thecritical role of social work education in the development of more inclusive social policy.